TEACHING ENGLISH VOCABULARY TO YOUNG LEARNERS - Imomova Sayyora (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Teaching English vocabulary to young learners is a crucial aspect of language education, as vocabulary knowledge is foundational for developing proficiency in a second language. This abstract explores effective strategies and approaches for teaching English vocabulary to young learners, focusing on the unique challenges and considerations that arise when working with children. The abstract discusses the importance of creating a stimulating and engaging learning environment to facilitate vocabulary acquisition, as well as the use of visual aids, interactive activities, and games to make the learning process enjoyable and effective. Furthermore, the abstract highlights the significance of repetition, context-based learning, and age-appropriate materials in reinforcing and expanding young learners' vocabulary. By incorporating these principles and techniques into English language teaching for young learners, educators can support their language development and foster a lifelong love for language learning.